Construção de grandes empreendimentos hidrelétricos: aspectos regulatórios, ambientais e principiológicos: o caso da UHE São Manoel - Falcão, Cristina Maria Vasconcelos (2017)
From a descriptive and analytical work of the regulatory structure built to planning the expansion of the hydroelectric power generation capacity and the insertion of the environmental paradigm in such policies, having as a focal point a concrete case - the construction of the HPP São Manoel, this dissertation aims to question whether the paths taken by public agencies - responsible for planning the electric sector and assessing the environmental impacts caused by the implementation of large hydroelectric projects - are capable of sustaining the technical deference necessary for the regular development of projects defined and designed for the expansion of hydropower generation capacity.More important than the technical correction of the studies carried out by public branchs, is the society's belief in the impartiality of the studies involved in the whole technical process (engineering and environmental) for the installation of hydroelectric projects, assuming that there is no contamination by political decisions. This belief is essential to guarantee stability to the expansion process desired by the Government. Thus, in the course of this study, is questioned the existence of an effective administrative procedure, either in the planning phase or in the environmental licensing process, to prevent controversy among the various stakeholders in the environmental licensing process. Finally, analyzing lawsuits that discuss the environmental licensing process of the HPP São Manoel, we identify that technical issues are relegated to the background, with emphasis on the use of constitutional and environmental principles, which are used to justify any argument, whether in favor or against, the construction of a hydroelectric plant.